1993
DOI: 10.1111/j.1365-2621.1993.tb09337.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron Distribution in Heated Beef and Chicken Muscles

Abstract: Distribution of iron in six fractions (water-soluble, water-insoluble, diffusate, hematin, total heme, and ferritin) of beef and chicken muscles hcatcd to 55, 70, 85, and 100°C was determined. Iron content decreased in water-soluble fractions and increased in water-insoluble fractions as temperature increased from 27°C to 100°C. Heme iron decreased more from 55°C to 85°C than from 27°C to 55°C or 85°C to 100°C. The increase in diffusate iron appeared to be less than the decrease in heme iron at each heating te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 25 publications
5
34
0
1
Order By: Relevance
“…The results agree with that reported by Ahn et al (2002) and Ferna´ndez-Lo´pez et al (2003). Iron is one of the main catalysts for oxidative rancidity in meat (Love, 1987) and non-haem iron has been reported to be the major catalyst in cooked meats and muscle foods because heat destroys haem iron and increase the level of non-haem iron (Han et al, 1993). Moreover, phospholipids are the primary substrates of lipid oxidation and are membrane components in close contact with the catalysts of lipid oxidation, which are located in the aqueous phase of the muscle cell (Gandemer, 1998).…”
Section: Changes Of Tbars Values During Storage Of Cooked Ground Porksupporting
confidence: 95%
“…The results agree with that reported by Ahn et al (2002) and Ferna´ndez-Lo´pez et al (2003). Iron is one of the main catalysts for oxidative rancidity in meat (Love, 1987) and non-haem iron has been reported to be the major catalyst in cooked meats and muscle foods because heat destroys haem iron and increase the level of non-haem iron (Han et al, 1993). Moreover, phospholipids are the primary substrates of lipid oxidation and are membrane components in close contact with the catalysts of lipid oxidation, which are located in the aqueous phase of the muscle cell (Gandemer, 1998).…”
Section: Changes Of Tbars Values During Storage Of Cooked Ground Porksupporting
confidence: 95%
“…In our conditions, heme and non-heme iron content results indicated that the iron-porphyrin moiety was quite resistant to thermal treatments even when heated at 90 C (Table 1) which was also in agreement with other works (Bou, Guardiola et al 2008, Kristensen, Andersen 1997, Han, Mcmillin et al 1993). …”
Section: Discussionsupporting
confidence: 80%
“…of respective samples were compared with those reported in other studies (Han et al, 1993;Schricker et al, 1982), the contents of heme and nonheme iron were slightly different. The differences might be attributed to factors such as varietal and methodological differences.…”
Section: Reference Analysesmentioning
confidence: 98%
“…Heme iron is of higher bioavailability (ú15%) than is nonheme iron (õ5%) (Hussain et al, 1965). In storage of cooked meat, nonheme iron has been implicated as a major catalyst of lipid peroxidation (Han et al, 1993;Love and Pearson, 1974). Hence, accurate and simple estimates for heme and nonheme iron contents have been in great demand not only for evaluation of iron bioavailability in different foods but also for assessment of storage stability of certain lipid-containing foods (Rhee and Ziprin, 1987).…”
Section: Introductionmentioning
confidence: 98%